alarm
Ask a question
Other
Clayton

A) -4(6 – 9) + 6(7 – 12) – 8 = b) -8 + {5 – [10 – 4(5 – 8 )]} =c) 7 – {8 + [13 – 2(-7 – 10)]} = d) 3 +[(4)(5) – 13] + (8 ÷ 4) – 9 = e) [4 – 6(10)] – [6(-4 + 7)] + 9(2 – 10) =f) (3² - 1)(4 + 6) – (3 + 1) =

answers: 1
Register to add an answer
Answer:

-4(6 – 9) + 6(7 – 12) – 8 =

−4×−3+6×(7−12)−8

−4×−3+6×−5−8

12+6×−5−8

12−30−8

−18−8

−26

-8 + {5 – [10 – 4(5 – 8 )]} =

-8+5-22

-25

7 – {8 + [13 – 2(-7 – 10)]} =

7-(8+13(13-2×(-17)))

7-(8+(13+34))

7-(8+47)

7-55

-48

3 +[(4)(5) – 13] + (8 ÷ 4) – 9

3+(20-13)+2-9

3+7+2-9

3

[4 – 6(10)] – [6(-4 + 7)] + 9(2 – 10)

(4-60)-(6×3)+9×(-8)

(-56)-18-72

-56-18-72

-146

25
bow out
For answers need to register.
275
cents
The time for answering the question is over
Contacts
mail@expertinstudy.com
Feedback
Expert in study
About us
For new users
For new experts
Terms and Conditions